Experimental tests of polymer reptation : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Physics at Massey University - Komlosh, Michal; Komlosh, Michal (Massey University, 1999)
Pulsed Gradient Spin Echo Nuclear Magnetic Resonance (PGSE-NMR) and rheology measurements were used to test whether the dynamics of entangled polymer chains in semidilute solution follow the reptation theory. Nine molar masses from 1 to 20 million daltons at a fixed concentration of 4.96% w/v along with a range of concentrations from 4.96% to 23.58% w/v at fixed molar mass of 3 million daltons were studied using PGSE-NMR techniques. The response to mechanical deformation of five different concentrations from 4.96% to 23.58% w/v at fixed molar mass of 3.9 million daltons was also studied. The distance and time scales accessed by PGSE-NMR were 20 to 1000 nm and 10 to 3000 ms respectively. As a result the mean square segmental motion over three reptation regimes was obtained and the reptation finger print, 〈(r(t) - r(0))〉 ~ t1/4, was observed. The resulting concentration and molecular weight scaling laws for the tube disengagement time, center of mass diffusion and the tube diameter, which were obtained in PGSE-NMR and rheology experiments, were found to be in good agreement with the reptation theory and its standard modifications, and a good quantitative fit to the mean square displacement was given by this theory. Local anisotropic motion of polymer chains at the level of the Rouse time was observed using double-PGSE NMR methods. These suggested a possible cooperative motion of polymer chains in entangled environment which challenges the basic assumptions of the reptation theory. Evidence of intra-chain spin diffusion was found. As a consequence relevant corrections incorporating the phenomenon into the PGSE-NMR data had to be made.
Keywords: Polymers; Polymer chains